NIKAH MENURUT PERSPEKTIF SAAD AD-DZARI'AH - Ma'ruf, Muhammad (LPPM STAI Muhammadiyah Probolinggo, 2023)
Abstract: This article intends to find out the background of the implementation of early marriage and the provisions of the implementation of early marriage according to Sadd al-Dzari'ah perspective in Diwek District, Jombang. This study uses a qualitative research process that goes directly to the field with the aim of clarifying the suitability between theory and practice using primary data located at the Office of Religious Affairs, Diwek District. The results of this study are that there are many early marriages that are factored in by the family environment, economic factors. From the perspective of Sadd al-Dzari'ah, there are several mafsadat caused by the first of the survival of the household, the vulnerability to domestic violence, the risk of dying during childbirth, the risk of divorce, interfering with education and work. Keywords: Marriage; Early Marriage; Saad Ad-Dzari,ah